Assessment of Toxic Heavy Metal Pollution in Urban Atmosphere in Tehran - Payamara, Jahangir (Asian Journal of Chemistry, 2010)
This work describes the methodological and experimental problems arising from toxic heavy metals constitute at Greater Tehran. Environmental monitoring for trace metal like lead, cadmium, zinc and copper in air, water, surface soil and food to assess the exposure of these heavy metals to population. The annual geometric mean concentration of these heavy metals show an increase in atmosphere and concentration of them were found to be higher in higher vehicular traffic areas but concentration of these heavy metals constitute in blood within the tolerance limits while teeth provide an index of cumulative exposure to heavy metals.